Test of the resistance of some clinical isolates of C.albicans against azoles and its relation with trailing growth phenomena - Adnan H. AL-Hamadani; Hayder abid al-Hussein Abbas (Al-Qadisiyah Journal of Pure Science, 2018)
The current  study aimed to detect role of Erg11 gene in the resistant of Candida albicans  toward azole antifungals , and its relationship with  the emergence of  resistant  or Trailing growth isolates  when testing  their drugs susceptibility against  azole (fluconazole, ketoconazole). A total of  120 specimens were collected from patients of both gender with  different source of admitted the general Hospital Hospital and Teaching materinaty  and children in Diwaniyah city during the period from December / 2012 to February / 2013.The isolation and identification result revealed that the isolation percent of C .albicans was 47.05 % incomparison with other different Candida species .The antibiotic susceptibity tests of C. albicans  showed  the presence of resistance  (38.89%) to fluconazole the most of sensitive isolates revealed  a trailing growth phenomena in the zone of growth inhibition of floconazole in a ratio 55.56% . While the resistance percent to ketoconazole was 27.78 % and the sensitive isolates showed the trailing   growth in a ratio (38.89%) . The statistical analysis showed a significant different (P<0.05) among testes treatment.The MICs values of fluconazole against C.albicans isolates were for resistance isolates and the trailing growth phenomena occurred at MICs value ≤ 8 Mg/mL within 24 hours of incubation while the values became ≥ 64 Mg/mL after 48 hours of incubation .There was a significant differences (p< 0.05) among tested treatments isolates incubated at 24 hours while there was no significant difference (P>0.05) at 48 hours of incubation.In respect with Ketoconazole , the resistance of C.albicans is increased after 48 hours of incubation at MICs values the trailing growth phenomena occurred when the MICs ≥  2 Mg/mL after 24 hrs of incubation , while it reached to ≥ 8 Mg/mL after 48 hrs of incubation . There was a significant differences (p< 0.05) among tested treatments isolates incubated of 24 hours while there was no significant difference (P>0.05) among treatments of 48 hours of incubation .